Effect of Motivation, Discipline and Perception of Leadership onthe Performance of Nutrition and MCH Healthcare Providersin Reducing Stunting Incidence Rate in Tegal - Murdaningsih, Novayanti; Ratna Rahayu, Sri; Maryati Deliana, Sri (Public Health Perspective Journal, 2018)
The role of healthcare providers in Community Health Center is required to provide professional services according their main duties. One of the achievements of nutritional program coverage in PHC is the success of healthcare providers in improving nutrition in the community, especially among babies and under-five children in accordance with the target set. The success of this program is also inseparable from the high motivation and discipline of nutrition and Mother & Child (MCH) healthcare providersso that it will have an impact on the improvement of performance, as well as the leadership role of the head of CHC in providing motivation and guidance to the healthcare provider in achieving the goals.This study aims to analyze the effect of motivation, work discipline and perception of the head of CHC leadership on the performance of nutrition and MCHhealthcare providers in reducing stunting (short) incidence rate among under-five children in the work area of CHCs in Tegal. This study was a quantitative study. This study used analytical survey design with cross sectional approach.The population of all nutrition and MCH healthcare providers in Tegal was 117 people and 60 samples were obtained by Slovin formula. The samples were obtained by purposive sampling technique. The instrument used was a questionnaire. Data analysis used Spearman test and Logistic Regression test. The result showed that there was a correlation between motivation (p = 0,001), work discipline (p = 0,003), and perception of leadership (p = 0,002) on the performance of nutrition and MCH healthcare providers. The logistic regression test was conducted with the result that motivation variable (p = 0,001 with OR = 5,239) and work discipline variable (p = 0,004 with OR = 4,459) had significant effect on the performance of nutrition health and MCH healthcare providers. The conclusion was thatnutrition and MCH healthcare providers with high motivation and high performance were 19 times greater compared to nutrition and MCH healthcare providers with low motivation and low performance in the work area of CHCs in Tegal.